English Department Students Collocation Abilities - Siusana Kweldju (TEFLIN, 1999)
In order to discover how well English Department students knowledge of collocations and how successful the communication strategies students used to hel them supply the expected collocations, 60 subjects were involved in this study. A fill-in-the-blank form test was administered to them to supply the collocates of the given nodes of selected collocations. The result of the analysis indicated that learners had a low mastery of collocations, and collocations need deliberate learning and teaching.